Perilaku Konsumen Kopi di Parewa Coffee Shop Kota Padang - Yeni Penora; Dian Fauzi; Alvindo Dermawan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Buyer behaviour is the thinking about how people, bunches, and organizations select, buy, utilize and utilize merchandise, administrations, thoughts or encounters to fulfil shopper needs and needs. The purchase decision is a process that goes through a series of activity stages that result in a decision. Coffee is one of the mainstay commodities in the economy of West Sumatra and one of the provinces that is a producer of coffee commodities for export. The purpose of this study is to describe the characteristics of coffee consumers and analyze the factors that influence the purchase of coffee at Parewa coffee shop. This research was conducted at Parewa coffee shop Bandar Purus, No.17 Padang City. The sample was taken by the Accidental Sampling method, with the number of samples taken as many as 60 respondents. The research was conducted at Parewa from June to August. The results showed that the characteristics of coffee consumers in Parewa coffee shop were male-dominated, aged 23-25 ​​years old, last high school education, which is still a student with an income of IDR < 2,500,000, unmarried marital status, and the frequency of purchasing coffee is two times. Partial hypothesis test (t-test) results indicate that personal, social, and psychological factors partially have a positive and significant effect on coffee consumer purchasing decisions at Parewa coffee shop. In contrast, cultural factors do not affect coffee consumer purchasing decisions at Parewa coffee shops.